Analisis Program Adiwiyata Mandiri dalam Menanamkan Sikap Peduli Lingkungan di SMP Negeri 17 Palembang - Muhamad Andri; Kms Badaruddin (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aims to: 1) Analyze and describe the concept of the Adiwiyata Mandiri program in SMP Negeri 17 Palembang. 2) Analyzing and describing the values ​​of Islamic education about environmental care contained in the Adiwiyata Mandiri Program at SMP Negeri 17 Palembang. 3) Analyzing the impact of the Adiwiyata Mandiri program on the caring behavior of students at SMP Negeri 17 Palembang. This study uses a qualitative approach to the type of case study research. Data sources use primary and secondary data. Data collection techniques by observation, interview and documentation. in analyzing data, researchers take an interactive model as its presentation. To get good results, researchers used data validity tests in the form of credibility, transferability, dependability and confirmability. The results of research at SMP Negeri 17 Palembang include: 1. The concept of the Adiwiyata Mandiri program at SMP 17 Palembang uses the concept of caring and cultured environment 2. The value of Islamic education about environmental care contained in the Adiwiyata Mandiri program is environmental care, an attitude of responsibility, honesty, mutual cooperation and saving attitude 3. The impact of the Adiwiyata Mandiri program is that students have an attitude of awareness to care for the environment.